Die Messung der langfristigen Entwicklung von Akquisitionen durch Familienunternehmen - Müller, Maximilian Philipp (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2013)
Most empirical studies in the field of finance state a negative impact to non-family firms when acting as a buyer in a transaction. Do acquisitions by family firms provide also negative, long‐term financial consequences to parent firms? This study analyses family versus non-family firms financial performance when a merger and acquisition (M&A) is completed. Based on a sample of 53 transactions, this article provides a comprehensive review of the financial performance of private German family firms, from 1997 to 2008. This study uses accounting based measures to examine the impact on corporate’s M&A performance, regarding growth, profitability and efficiency factors and for the first time data from cash flow statements and working capital measures of private family firms. The findings demonstrate that even before the transaction family businesses show a financial performance above average, compared to its direct peer companies. Subsequently an acquisition the data implies that family ownership has a positive and sustainable influence on company’s financial performance. Therefore corporate M&A and existing recessions during the period of investigation cannot prevent family firms from improving their earning power and generating sustainable and profitable growth.

Familienunternehmen und Akquisitionen – ein Erfolgsmodell? Dieser Frage widmet sich die vorliegende Arbeit und untersucht die langfristige Akquisitionsperformance privater deutscher Familienunternehmen sowohl im Selbst-; als auch im Branchenvergleich anhand ausgewählter jahresabschlussbezogener Kennzahlen. Anhand 53 Transaktionen, in der Zeit von 1997 bis 2008, bei denen Familienunternehmen als Käufer auftreten, wird die Performanceveränderung auf Basis einer ex ante/ ex post&-Analyse sowie einer komparativen Objektanalyse betrachtet. Neben einer Kombination jahresabschlussorientierter, betriebswirtschaftlicher Indikatoren, die die Merkmale Wachstum, Profitabilität und Effizienz abbilden, werden erstmalig auch Informationen wie Kapitalflussrechnung und das Umlaufvermögen in der Analyse berücksichtigt. Im Ergebnis zeigt sich, dass Akquisitionen auf Familienunternehmen positiv und stabilisierend einwirken. Familienunternehmen dokumentieren bereits vor dem Zusammenschluss eine überdurchschnittliche Performance gegenüber ihren jeweiligen Branchenunternehmen und können durch Akquisition und trotz Rezession im Untersuchungszeitraum ihre vorteilhafte Position durch profitables Wachstum weiter ausbauen.
Mergers and Acquisitions by Private German Family Firms: A Long-Term Study
Keywords: Familienbetrieb; Leistungsmessung; Unternehmenserfolg; 330 Wirtschaft